KAJIAN PENENTUAN NILAI CBR TANAH MENGGUNAKAN DYNAMIC CONE PENETROMETER PADA PEMBANGUNAN RUAS JALAN MAMBRUK-KADAMBER KABUPATEN FAKFAK - Muhammad Yunus; La Resky H. Nurfafen; M. Afdal R. Rum (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2022)
In the road planning, one of the parameters needed is the value of California Bearing Ratio (CBR). the value of CBR is used as a parameter to determine the condition of the subgrade. The study was conducted to determine the CBR value and the percentage of the subgrade bearing capacity criteria on the MambrukKadamber road, Fakfak Regency, West Papua. The method used in this study is a field survey using a Dynamic Cone Penetrometer (DCP) on a 1,9 km long track and divided every 50 meters so that the number of test points is 40 points, then the test data are analyzed using the PUPR and Kleyn methods. From the results of the analysis, the largest CBR value is 31,43% and the smallest 4,66% if analyzed using the PUPR method and when using the Kleyn method the largest CBR value is 22,23% and the smallest 3,51% with the avarege difference between both method is 3,27%. It is also known that as many as 10% of points still have poor soil bearing capacity criteria